Sankcje za wyłączenie gruntów leśnych z produkcji w świetle doktryny i orzecznictwa – głos w dyskusji - Trela, Anna (Studia Prawa Publicznego, 2024)
The Act of 3 February 1995 on the protection of agricultural and forest land in Article 28 provides for sanctions for the exclusion of agricultural and forest land from production contrary to the provisions of the Act (paragraph 1) or without a decision authorising the exclusion in the case of land which has been designated in the local spatial development plan for non-agricultural or non-forest purposes (paragraph 2). In the first case, the authority shall set a fee of double the amount due, and in the second case, the authority shall issue a ‘legalisation’ decision based on Article 12 and increase the amount due by 10%. The provision of Article 12(6) of the Law on the Protection of Agricultural and Forestry Land also provides for the possibility of reducing the amount due by the value of the land in accordance with the market price. The possibility of applying Article 12(6) in the case indicated in Article 28(2) of the Agricultural and Forest Land Protection Act is problematic. It should be emphasised that the content of the provisions in question has not changed since 1995. They were treated as two different legal situations and did not give rise to any doubts in practice or jurisprudence. It was accepted that the authority obliged to issue a legalisation decision had the right to apply Article 12(6). The position of administrative courts has been different for several years now, according to which the provisions of Article 28(1) and (2) should be treated jointly, as they both provide for sanctions, although they constitute separate editorial units. In the doctrine approval is also found for the new views of the judicature accepting that in the case indicated in Article 28(2) it is not possible to apply a reduction in the amount due by the value of the land. The practice presented by the regional directorates of the State Forests, on the other hand, is very diverse. The problem that has arisen requires that the various positions be voiced and evaluated.